THE EFFECT OF MAKE A MATCH (MAM) TYPE MODEL AND BAMBOO DANCE TYPE MODEL THROUGH COOPERATIVE LEARNING ON STUDENTS MOTIVATION - Mohamad Nur Fauzi; Budi Usodo; Sri Subanti (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2017)
Students motivation plays an important role in every learning process. Lacking in Make A Match (MAM) type model in mathematics teaching has become the justification in finding the solution for the crowded situation. This research used quasi experimental research design. The samples used were 60 students and they were requested to respond a set of motivation questionnaire. In addition, the students activity data was obtained from the observation sheet. T-test was used to determine the difference in motivation between experimental and control group. The result revealed that, the influence of the Make A Match (MAM) Type Model And Bamboo Dance Type Model Through Cooperative Learning on the motivation of the students.